2005
DOI: 10.1108/13639510510614528
|View full text |Cite
|
Sign up to set email alerts
|

Variation in officer downtime: a review of the research

Abstract: PurposeTo summarize and compare both the methodology and findings of existing studies of patrol officer workload that have contributed to what is known about “downtime” (time not responding to citizen calls for service), and provide more standardized estimates of downtime for comparison purposes.Design/methodology/approachA total of 11 studies of police workload published between 1970 and 2001 that used data collected through either dispatch records or systematic social observations of police officers, and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 14 publications
3
33
0
1
Order By: Relevance
“…Fifth, the present study joins prior studies (Famega, 2005;Famega et al, 2005;Johnson, 2008;Moskos, 2008;Smith et al, 2001), suggesting that officer free patrol time is being underutilized in many law enforcement agencies today. This is time that could be better spent on officer-initiated activities that have shown some success in reducing crime and improving public safety, such as directed patrols at hot spot locations, proactive stops looking for guns, proactive stops looking for drunk drivers, and stops and surveillance on known repeat offenders (Skogan & Frydl, 2004).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Fifth, the present study joins prior studies (Famega, 2005;Famega et al, 2005;Johnson, 2008;Moskos, 2008;Smith et al, 2001), suggesting that officer free patrol time is being underutilized in many law enforcement agencies today. This is time that could be better spent on officer-initiated activities that have shown some success in reducing crime and improving public safety, such as directed patrols at hot spot locations, proactive stops looking for guns, proactive stops looking for drunk drivers, and stops and surveillance on known repeat offenders (Skogan & Frydl, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…The prior research, however, has suggested that few patrol officers utilize this free patrol time to engage in proactive policing activities (Famega, 2005;Moskos, 2008;Smith, Frank, & Novak, 2001), and that patrol officers are rarely given clear or specific directions about how to use this free patrol time Johnson, 2010).…”
mentioning
confidence: 99%
“…Early research by Cumming, Cumming, and Edell (1985, 219) indicated that few calls for service are "law enforcement" related; most calls require police officers "to exercise their amateur talents." These findings have been consistently supported by other scholars (Famega 2005;Frank, Brandl, and Watkins 1997).…”
Section: Introductionsupporting
confidence: 86%
“…Thus, "the symbolism of the aggressive crime fighter" (Herbert 2001, 66) provides policing with a salient social reality discussed by Barbalet (1999). The reality of policing, however, is that the opportunity to deal with exciting events or serious crime is rare (Cumming, Cumming, and Edell 1985;Famega 2005;Frank, Brandl, and Watkins 1997). Research in the UK from three and four decades ago suggested that the opportunity to engage in real police work is denied to officers (Cain 1973), and the actual work of patrol officers -patrolling or driving around with no particular goal -is considered a waste of time (Holdaway 1983).…”
Section: Police and Boredommentioning
confidence: 99%
“…In addition, street-level actions enacted by police officers can exhibit a great deal of variability even within single interventions. Police officer actions are not situationally dictated, as research suggests as much as 37% to 86% of a patrol officer's shift comprises "uncommitted time" not spent on responding to calls for service, making arrests, or engaging in other administrative duties (Famega, 2005). Hence, officers enjoy a great deal of latitude when choosing how to address incidents of concern, with a number of appropriate enforcement decisions available in most instances (Schafer, Carter, Katz-Bannister, & Wells, 2006).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%